The cGAS-STING signaling in cardiovascular and metabolic diseases: Future novel target option for pharmacotherapy - Patrick Kwabena Oduro; Xianxian Zheng; Jinna Wei; Yanze Yang; Yuefei Wang; Han Zhang; Erwei Liu; Xiumei Gao; Mei Du; Qilong Wang (Elsevier, 2022)
The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling exert essential regulatory function in microbial-and onco-immunology through the induction of cytokines, primarily type I interferons. Recently, the aberrant and deranged signaling of the cGAS-STING axis is closely implicated in multiple sterile inflammatory diseases, including heart failure, myocardial infarction, cardiac hypertrophy, nonalcoholic fatty liver diseases, aortic aneurysm and dissection, obesity, etc. This is because of the massive loads of damage-associated molecular patterns (mitochondrial DNA, DNA in extracellular vesicles) liberated from recurrent injury to metabolic cellular organelles and tissues, which are sensed by the pathway. Also, the cGAS-STING pathway crosstalk with essential intracellular homeostasis processes like apoptosis, autophagy, and regulate cellular metabolism. Targeting derailed STING signaling has become necessary for chronic inflammatory diseases. Meanwhile, excessive type I interferons signaling impact on cardiovascular and metabolic health remain entirely elusive. In this review, we summarize the intimate connection between the cGAS-STING pathway and cardiovascular and metabolic disorders. We also discuss some potential small molecule inhibitors for the pathway. This review provides insight to stimulate interest in and support future research into understanding this signaling axis in cardiovascular and metabolic tissues and diseases.